2016
DOI: 10.1620/tjem.240.25
|View full text |Cite
|
Sign up to set email alerts
|

Common Polymorphisms in<i> GSTA1</i>, <i>GSTM1</i> and <i>GSTT1 </i>Are Associated with Susceptibility to Urinary Bladder Cancer in Individuals from Balkan Endemic Nephropathy Areas of Serbia

Abstract: Balkan endemic nephropathy (BEN) is a chronic familial form of interstitial nephritis that might eventually lead to end stage renal disease. This nephropathy affects individuals living along of the Danube River and its tributaries in Serbia, Bosnia, Croatia, Bulgaria and Romania. The increased incidence of urinary tract tumors in the BEN areas is well described, but its specific genetic predisposition is still unclear. Certain nephrocarcinogenic compounds, including those associated with BEN, are metabolized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Characteristics of the included studies reporting risk or oncologic outcomes of AA-UTC Tables 1 and 2 summarize the characteristics of the 25 studies reporting risk or oncologic outcomes of AA-UTC. [66][67][68] Twenty-four were peer-reviewed articles published from 1991 to 2020, [35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][66][67][68] and one was a master's thesis completed in 2011. 43 Among them, 18 were cohort studies 37,38,[40][41][42][43][44]46,[48][49][50][51][52][53][54][55]56,68 and seven were case-control studies.…”
Section: Comparison Of the Included Studies Between The Present And Previous Systematic Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies reporting risk or oncologic outcomes of AA-UTC Tables 1 and 2 summarize the characteristics of the 25 studies reporting risk or oncologic outcomes of AA-UTC. [66][67][68] Twenty-four were peer-reviewed articles published from 1991 to 2020, [35][36][37][38][39][40][41][42][44][45][46][47][48][49][50][51][52][53][54][55][56][66][67][68] and one was a master's thesis completed in 2011. 43 Among them, 18 were cohort studies 37,38,[40][41][42][43][44]46,[48][49][50][51][52][53][54][55]56,68 and seven were case-control studies.…”
Section: Comparison Of the Included Studies Between The Present And Previous Systematic Reviewsmentioning
confidence: 99%
“…37,38,41,42,44,51,66 The outcome of interest in 15 studies was risk of primary UTC, including UC, [35][36][37][38][39][40][41][42][43][44][45][46]66 RCC, 37,41,43,67 and BC. 47 In RTRs, post-transplant malignancies were reported. Ten [48][49][50][51][52][53][54][55][56]68 studies reported oncological outcomes of primary AA-UC after surgery; nine [48][49][50][51][52][53][54]56,68 of them reported recurrence, and five 50,[54][55][56]68 of them reported survival outcomes.…”
Section: Comparison Of the Included Studies Between The Present And Previous Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control cases were randomly selected from among participants. The genotypes GSTM1-null and GSTT1-null, produced no GSTM1 and GSTT1 protein and consequently completely lack GSTM1 and GSTT1 enzymatic activity (Matic et. al., 2016).…”
Section: Gstm1 and Gstt1 Genotypingmentioning
confidence: 99%
“…al., 2013;Yajie et. al., 2016;Matic et. al., 2016) which include GSTM1 and GSTT1 class deletion polymorphism (GSTM1-null and GSTT1-null).…”
Section: Other Analyses Of S Haematobium Infection Inmentioning
confidence: 99%